Draft Annual Plan 2005-2006 Volume - I Government of Sikkim - Planning Commission (Planning Commission, 2005)
Sikkim is a strategic, small hilly state in the Eastern Himalayas with total geographical area of 7096 sq. Kms and total population of 5,40,493 as per 2001 census. The lofty mountains, perennial glaciers, lush green hills, valleys and the rich biodiversity constitute the magnificent watershed both tor sustainable social and economic development and also for enriching the traditional and cultural heritage of the people of Sikkim. The State joined the democratic main stream of the Indian Union only 29 years ago in 1975. The democratic process have generated ample social and economic security to the masses, their choices are broadened and their hopes transformed into opportunities. The journey so far has been rewarding and the process of development satisfactory.
Development Planning, Economic Reforms and North-Eastern Council Affairs Department
Development Planning, Economic Reforms and North-Eastern Council Affairs Department